Humanistic nursing with characteristics of Traditional Chinese Medicine in the nursing ward rounds of a patient after total knee arthroplasty (1例人工全膝关节置换术后患者中医特色人文关怀护理查房体会) - FAN Weiwei (范薇薇); WANG Qiujie (王秋洁) (Association of Integrative Nursing, 2023)
Humanistic　care has been considered a core element of high-quality nursing service. This paper summarized the practice of Humanistic nursing with characteristics of Traditional Chinese Medicine in the nursing ward rounds of a patient after total knee arthroplasty (TKA). Nursing ward rounds with characteristics of Traditional Chinese Medicine was conducted, and patient's needs on pain control, relief of anxiety, prevention of compilations and functional exercise were analyzed before implementation of targeted interventions and humanistic care. It may help to improve nurse awareness and practice skills of humanistic nursing with characteristics of Traditional Chinese Medicine in the nursing ward rounds. (人文关怀属于优质护理服务范畴。本文总结l例人工全膝关节置换术后患者中医特色人文关怀护理查房经验, 通过开展具有中医特色的人文关怀护理查房, 分析患者术后疼痛、焦虑、并发症、饮食和功能锻炼需求并制定护理干预措施, 以缓解患者临床症状。该模式的对促进全院护理人员的关怀意识及能力提升具有积极意义。)